EFEKTIVITAS PELATIHAN MENYUSUI ONLINE MELALUI ZOOM MEETING TERHADAP PENGETAHUAN MAHASISWA KEPERAWATAN - Regina Natalia; Savitri Gemini; Wardah (CV. ADIBA AISHA AMIRA, 2022)
Nursing students are included in the support group for breastfeeding mothers. It is important that they have adequate knowledge about breastfeeding. Learning strategies that can promote breastfeeding theory and practice can be achieved through online learning through the media zoom meeting. This study aims to identify the effectiveness of online breastfeeding training through zoom meetings on knowledge level of nursing students. The study design used a quasi- experimental study involving 34 nursing students who were divided into the intervention group and the control group. Bivariate analysis using independent t-test showed a significant difference (p=0.001) in the level of knowledge between both groups after being given different intervention. This study recommends the use of a variety of learning media in the form of zoom meetings for distance learning and can meet the theoretical and practical needs of nursing students